Serial C-reactive Protein and Blood Culture in the Diagnosis of Neonatal Sepsis among Babies with Risk Factors for Sepsis at Uniosun Teaching Hospital, Osogbo, Nigeria - Omoboyeje, A O; Adebami, O J; Oyedeji, O A; Ademisoye, A; Kayode, V O (West African journal of medicine, 2025)
Neonatal sepsis (NNS) contributes significantly to morbidity and mortality among newborns, especially in developing countries. Early identification of risk factors is crucial for prompt diagnosis and treatment. This study aimed to investigate utility of serial C-reactive protein (CRP) and blood culture in the diagnosis of neonatal sepsis (NNS) among babies with risk factors for sepsis. All consecutive term babies with maternal and/or neonatal risk factors for sepsis with or without initial symptoms were studied. Blood culture was done for all the participants. The CRP I was done at admission, CRP II at 48 hours and CRP III at 72 hours (a total of 3 samples). The value of CRP ≥10mg/l was considered abnormal. Of 106 participants, 35 (33%) had positive blood cultures, with Staphylococcus aureus being the prevalent organism. The sensitivity of CRP at the cut off ≥10mg/l was 60%, 69.7%, and 66.7% for CRP I, CRP II and CRP III, with negative predictive value (NPV) of 73.6%,72.2% and 73.8%, respectively. Abnormal temperature, respiratory distress and convulsion at presentation were significantly associated with positive blood culture (p= 0.002, 0.014 and 0.009, respectively). Logistic regression identified abnormal temperature and delivery outside the hospital facility as being significantly related to elevated CRP values (p= 0.027, 0.016). These findings highlight the importance of utilization of serial CRP tests in the early detection of sepsis in neonates with risk factors.